Entre o digital e o não digital: um estudo dos usuários do Arquivo do Centro de Ciências da Saúde da Universidade Federal da Paraíba - Souza, Emilia Eulina Pereira de (2020)
This work brings reflections on the archival practices in the digital and non-digital archives, understanding the transformations in the supports of the documents. The theme of User Studies (US) is gift in Information Science, in view of the perception that these are fundamental individuals in the informational processes. These studies are primordial for the recognition of the use of the files, seeking the improvement in the attendance, demands, needs, behavior, etc. From these perspectives, the general objective is to understand the information needs of the users of the archive of the Health Sciences Center (CCS) of the Federal University of Paraíba (UFPB), having as a problem the following question: what would be the appropriate ways to identify and meet the questions of seeking information from users of the archive of the Archive of the Health Sciences Center (CCS) of the Federal University of Paraíba (UFPB)?Specifically, it was sought to trace the CCS/UFPB file user profile, identifying the main information needs of the users, as well as verifying that the document management procedures of the CCS/UFPB file are compatible to meet the information needs of users. Its methodological configuration is based on bibliographical, descriptive, exploratory, quantitative-qualitative, using an alternative approach, with the use of questionnaires. he beginning of the operation of the research done with the users, belonging to the internal environment of the CCS/UFPB management file, was feasible, to draw the profile of internal users. The second step was to identify the main information needs of users such as use of sources, services and information systems. When verifying that the document management procedures of the CCS/UFPB file are compatible to meet the information needs of the users.